Pembuatan Desain & Rab Ruang Parkir Komunal: Communal Parking Space Design & Rab - Choirul Amin; Ery Ashary (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
In the residential area of ​​RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City, many people have vehicles, especially 4-wheeled vehicles, which cannot be accommodated in their yard due to limited land or plots owned. On the other hand, there are public facilities at RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City which are neglected and not utilized which are later expected to become communal parking areas for community members. The goals of community service related to the design and RAB of communal parking spaces in RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City, include: creating a functional and good shared parking area so that residents' vehicles are no longer parked in the neighborhood road area, so that it will participate in organizing and beautifying and improving the quality of the environment. The method used in community service related to the design and RAB of communal parking spaces in RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City is through field surveys or locations where the data is then collected, designed or designed, then a budget plan is made or WED. The expected results of community service related to the design and RAB of communal parking spaces consist of 3 things namely: first the participative level of the community towards their environment, secondly the design drawings of representative communal parking spaces, thirdly the budget plan or RAB to carry out the construction of communal parking spaces in RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City. The output of community service related to the design and RAB of communal parking spaces in RT 09 RW IX, Sendang Mulyo Village, Tembalang District, Semarang City is in the form of a report containing pictures and RAB which will be submitted to the community in the neighborhood and to LPM UNTAG Semarang as evidence administrative responsibility.